Deviations From the Ideal Plasma Volume and Isolated Tricuspid Valve Surgery—Paving the Way for New Risk Stratification Parameters - Hasimbegovic, Ena; Russo, Marco; Andreas, Martin; Werner, Paul; Coti, Iuliana; Wiedemann, Dominik; Kocher, Alfred; Laufer, Günther; Hofer, Benedikt S.; Mach, Markus (Frontiers in Cardiovascular Medicine, 2022)
Background Congestion and plasma volume expansion are important features of heart failure, whose prognostic significance has been investigated in a range of surgical and non-surgical settings. The aim of this study was to evaluate the value of the estimated plasma volume status (ePVS) in patients undergoing isolated tricuspid valve surgery. Methods This study included patients who underwent isolated tricuspid valve surgery at the Vienna General Hospital (Austria) between July 2008 and November 2018. The PVS cut-off was calculated using ROC analysis and Youden's Index. Results Eighty eight patients (median age: 58 [IQR: 35-70] years; 44.3% male; 75.6% NYHA III/IV; median EuroSCORE II 2.65 [IQR: 1.70-5.10]; 33.0% endocarditis-related regurgitation; 60.2% isolated repair; 39.8% isolated replacement) were included in this study. Patients who died within 1 year following surgery had significantly higher baseline ePVS values than survivors (median ePVS 5.29 [IQR: −1.55-13.55] vs. −3.68 [IQR: −10.92-4.22]; p = 0.005). During a median actuarial follow-up of 3.02 (IQR: 0.36-6.80) years, patients with a preoperative ePVS ≥ −4.17 had a significantly increased mortality (log-rank p = 0.006). Conclusions ePVS is an easily obtainable risk parameter for patients undergoing isolated tricuspid valve surgery capable of predicting mid- and long-term outcomes after isolated tricuspid valve surgery.